Dampak Profitabilitas sebagai Intervening pada Kepemilikan Institusional terhadap Kualitas Laba - Supami Wahyu Setiyowati; Mochamad Fariz Irianto (Universitas Winaya Mukti, 2020)
Earnings quality refers to reported earnings to predict a firm’s future earnings, which is essential for the investor’s decision-making to understand its financial health. The purpose of this study was to determine the impact of profitability as an intervening variable between institutional ownership to earnings quality. This study's population was manufacturing companies in the consumer goods industry listed on the IDX for the 2017-2019 period. The sampling method is based on criteria. The samples in this study were 15 issuers. Data analysis techniques using Smart Pls. The results showed that institutional ownership affected earnings quality. Profitability was not proven as an intervening variable on the relationship between institutional ownership and earnings quality. This finding implied that institutions that had share ownership in the company increased their supervision to reduce the manager's opportunistic behaviour.